Understanding Community Media: SAGE Publications - Howley, Kevin (SAGE Publications, Incorporated, 2009)
A cutting edge examination of community media from theoretical, empirical, historical, and practitioner perspectives, with essays on subjects like women′s video collectives in India, indigenous radio in Colombia, street newspapers in Canada, and independent media in Nigeria.